Technical recommendations for artificial insemination in sheep - Gibbons, Alejandro Eduardo; Fernandez, Jimena; Bruno Galarraga, Maria Macarena; Spinelli, María Victoria; Cueto, Marcela Isabel (Colégio Brasileiro de Reprodução Animal, 2019)
Artificial insemination (AI) was the first important biotechnology applied to improve the genetics of farm animals. It allows the rapid and massive diffusion of desirable characteristics of males with high productive potential. We describe the different types of estrus induction and synchronization techniques and the use of the AI with fresh, chilled or frozen semen. Through the adequacy of the protocols of estrus synchronization and AI to the different production systems, the efficient use of reproductive techniques is possible, reaching acceptable pregnancy rates. Summary of reproductive results obtained using cervical and laparoscopic AI are presented